Binary alloy of functionalized small-molecule acceptors with the A–DA′D–A structure for ternary-blend photovoltaics displaying high open-circuit voltages and efficiencies. Issue 43 (12th October 2022) - Lin, Yu-Che; Chen, Chung-Hao; Lin, Heng; Li, Meng-Hua; Chang, Bin; Hsueh, Ting-Fang; Tsai, Bing -Shiun; Yang, Yang; Wei, Kung-Hwa
Abstract : Binary acceptor alloys based on two A′′–D′A′D′–A′′ small molecule acceptors having the same core but different end groups provided OPV with high PCE, V oc and stability. Abstract : Binary acceptor alloys based on two A′′–D′A′D′–A′′ small-molecule acceptors having the same core structures and side chains but different conjugation end groups, namely, BTPO-NF and BTPO-F were synthesized and blended with the polymer PM6 for forming ternary blends of organic photovoltaics (OPVs) displaying high open-circuit voltages ( V OC ), power conversion efficiencies (PCEs), and stability. Both BTPO-NF and BTPO-F possessed the same alkoxy chains, which increased the energies of their lowest unoccupied molecular orbitals (LUMOs) and mutual miscibility. After varying the amount of the two acceptor ratios in the ternary-blend system, we found that the optimum device performance could be achieved in the case of alloy acceptors with one major (BTPO-NF) and one minor (BTPO-F) acceptor component; the PM6:BTPO-NF:BTPO-F (1 : 1 : 0.2 wt) ternary-blend device provided the highest PCE of 18.0% with a high V OC of 0.97 V, with the PM6:BTPO-NF and PM6:BTPO-F (1 : 1.2 wt) devices displaying PCEs of 17.11% and 16.23, respectively. The enhancement in the PCE value of the PM6:BTPO-NF:BTPO-F (1 : 1 : 0.2 wt) ternary-blend device resulted from the increase in the photocurrent of the device with the optimized active layer morphology induced by the alloy acceptor structures as compared to that of the binary-blend devices. Thus, the strategy of molecular engineering of two acceptors with the same core and side chains for increasing their mutual miscibility but different degrees of conjugation for broadening the light absorption allowed the formation of binary acceptor alloys with disparite ratios, laying the foundation for the pursuit of OPVs with high values of V OC, high PCEs, and high stabilities.